Balancing research, monitoring, and action to recover Canada's species at risk. Issue 132 (June 2022) - Buxton, Rachel T.; Hamit, Shamri; Geauvreau, Joshua J.W.; Davis, Sierra; Smith, Paul A.; Bennett, Joseph R.
Abstract: Despite accelerating biodiversity loss, conservation efforts suffer from serious resource deficiencies. This requires conservation managers to strike a challenging balance between direct action, which is needed to avoid further biodiversity loss, and research and monitoring, which provide the information needed for more effective action. Here, we explore different types of management tasks in action plans for legally protected species at risk of extinction in Canada, and determine the proportion of effort allocated to research and monitoring. We found that 46% of management tasks in action plans were research and monitoring, largely involving area-based management planning (12%), population monitoring (12%), and research examining conservation actions and techniques (11%). Of the management tasks that were categorized as actions, the largest number (35%) were related to education and awareness. The proportion of management tasks allocated to research and monitoring were highest for species with higher risk of extinction (i.e., Endangered vs. No Status). This suggests that either less is known about these species or that fear of negative outcomes for especially imperiled species may deter necessary actions. Our findings underscore the need to carefully examine the value of collecting new information and consider the optimal allocation of resources between action and research and monitoring to maximize the recovery of species at risk of extinction. Highlights: Rapid and effective conservation action is needed to prevent species extinction. Conservation programs must balance resources between action, research, and monitoring. Half of management tasks for protected Canadian species are research and monitoring. Allocation of action tasks were lowest for species with higher risk of extinction. Managers must carefully examine the value of collecting new information vs acting.